A CLINICAL CASE OF URINARY-COLONIC-VAGINAL-SKIN FISTULA - Довбета, Евгений Владимирович; Ооржак, Орлан Валерийович; Полутарников, Евгений Александрович; Мозес, Вадим Гельевич; Шапкин, Александр Анатольевич (Medicine in Kuzbass, 2020)
Urogenital fistulas are an extremely serious complication that requires high-quality surgical correction. This pathology negatively affects all aspects of a woman’s quality of life - sexual, psychological, physical and social. Currently, in the structure of the causes of urogenital fistulas, gynecological operations have come first. The main pathogenesis of fistula development during surgical treatment is associated with iatrogenic mechanical, thermal and/or ischemic tissue damage and ligature through the tissues of the vagina and bladder. Despite the emergence of new diagnostic methods, new synthetic suture materials and endoscopic techniques, the diagnosis and treatment of urogenital fistulas remains an extremely difficult task. The article presents a clinical case that clearly illustrates the complexity of the diagnosis and treatment of this pathology.